Three-dimensional network polymer gel electrolyte, positive plate and solid-state lithium battery

By using three -dimensional network polymer gel electrolytes in lithium metal batteries, using ultraviolet light mulpy sulfonate spontaneously generate optical chemical free radicals for in -situ aggregation to form a three -dimensional network structure, solving the safety of liquid electrolyte in lithium metal batteries The problem of incompatibility between hidden dangers and gel electrolytes has achieved higher cycle life and safety performance.

CN119340469APending Publication Date: 2025-01-21HUNAN LIFANG NEW ENERGY SCI & TECH
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411504009.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In existing lithium metal batteries, liquid electrolytes have safety hazards, such as the growth and side reactions of lithium dendrites, which lead to short circuits, combustion or explosions, and some initiators are required for in-situ polymerization methods of gel electrolytes. The type is incompatible with the lithium metal negative electrode and is prone to side reactions.

Method used

A three-dimensional network polymer gel electrolyte is used, which is composed of 80 to 98% organic solvent, 5 to 15% lithium salt, 2 to 8% lignosulfonate, 2 to 10% polymerized monomers and 2 to Composed of 8% ionic liquid, photochemical free radicals are spontaneously generated by lignosulfonate under UV light, triggering in-situ polymerization to form a three-dimensional network structure, avoiding the use of initiators.

Benefits of technology

Improve the cycle life and safety performance of lithium metal batteries, inhibit the growth of lithium branches, avoid the occurrence of side effects, and enhance the mechanical strength and electrochemical stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005103284450000081
    Figure BDA0005103284450000081
Patent Text Reader

Abstract

The invention provides a three-dimensional network polymer gel electrolyte, a positive plate and a solid-state lithium battery. The three-dimensional network polymer gel electrolyte comprises 80-98% of an organic solvent, 5-15% of a lithium salt, 2-8% of lignosulfonate, 2-10% of a polymeric monomer and 2-8% of an ionic liquid, and the polymeric monomer is selected from acrylamide, polyethylene glycol dimethacrylate, 3-(methacryloyloxy) propyl trimethoxy silane or tetrahydrofurfuryl acrylate and the like. Under ultraviolet light, lignosulfonate can spontaneously generate quinonyl photochemical free radicals and hydroxyl photochemical free radicals in a mixed solution of ionic liquid and specific polymer monomers, and under the action of the photochemical free radicals, the lignosulfonate reacts with unsaturated double bonds on a polymer through phenolic groups, so that the photochemical free radicals are formed. The gel electrolyte with a three-dimensional network structure is formed, the mechanical strength can be improved, the growth of lithium dendrites in a lithium metal battery can be inhibited, and the metal lithium battery containing the gel electrolyte has excellent cycle life and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid-state lithium metal batteries, and in particular relates to a three-dimensional network polymer gel electrolyte, a positive electrode sheet and a solid-state lithium battery. Background Art

[0002] As the third generation of energy storage devices after nickel-cadmium batteries and nickel-metal hydride batteries, lithium-ion batteries have been widely used in consumer electronics, military equipment, and grid-scale energy storage systems. With the development of society, the practical application of lithium-ion batteries has faced challenges such as limited energy density and insufficient safety performance. At present, lithium metal anodes have attracted the attention of researchers due to their high specific capacity. Using lithium metal as anode is one of the most effective strategies to improve the energy density of lithium batteries. However, liquid lithium metal batteries have certain safety hazards, such as electrolyte leakage, lithium dendrite growth, and uncontrollable side reactions, which can cause battery short circuits, combustion, and even explosions.

[0003] In recent years, gel electrolytes have attracted widespread attention from researchers. Compared with liquid electrolytes, gel electrolytes have a certain mechanical strength, which can inhibit the growth of lithium dendrites and prevent short-circuit problems. At the same time, it is also not easy to leak, which further improves the safety performance of lithium metal batteries. Therefore, the lithium metal anode is combined with a stable and non-leaking gel electrolyte to prepare a quasi-solid-state lithium metal battery, which can have both higher energy density and greater safety. However, some of the initiator types required for the in-situ polymerization method of gel electrolytes are incompatible with the lithium metal anode, and side reactions are prone to occur, leading to the formation of lithium dendrites. Therefore, the development of an in-situ polymerization gel electrolyte that does not require the addition of an initiator is a current research hotspot. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a three-dimensional network polymer gel electrolyte, a positive electrode sheet and a solid-state lithium battery. The solid-state lithium battery assembled with the positive electrode sheet prepared by the electrolyte has a higher cycle life and safety performance.

[0005] The present invention provides a three-dimensional network polymer gel electrolyte, which comprises, by mass fraction, 80-98% organic solvent, 5-15% lithium salt, 2-8% lignin sulfonate, 2-10% polymerized monomer and 2-8% ionic liquid;

[0006] The polymerizable monomer is selected from one or more of polyethylene glycol diacrylamide, polyethylene glycol diacrylate, methyl methacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, vinyl acetate, vinyl vinyl sulfite, acrylamide, ethyl acrylate, tetrahydrofuran acrylate, 3-(isomethacryloyloxy)propyltrimethoxysilane, vinyl-tri(methylethylketoxime)silane and isooctyl acrylate.

[0007] Preferably, the lignin sulfonate is selected from one or more of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate.

[0008] Preferably, the ionic liquid is selected from imidazoles and / or pyrroles;

[0009] The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium perchlorate, lithium bisoxalatoborate, lithium tetrafluorooxalatophosphate and lithium difluorobisoxalatophosphate.

[0010] Preferably, the organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl propionate, fluoroethylene carbonate, and methyl trifluoroethyl carbonate.

[0011] The present invention provides a positive electrode sheet, which is prepared by the following method:

[0012] The positive electrode current collector provided with the positive electrode active material layer is immersed in the three-dimensional network polymer gel electrolyte described in the above technical solution, taken out and photocured to obtain a positive electrode sheet.

[0013] Preferably, the immersion time is 3 to 5 hours; the immersion temperature is room temperature 20°C to 30°C.

[0014] Preferably, the ultraviolet light source used in the photocuring is 365 nm and the intensity is 160-180 mW cm -2 ; The light curing time is 15 to 25 minutes.

[0015] Preferably, the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder;

[0016] The positive electrode active material is a positive electrode active component coated with an oxide solid electrolyte; the positive electrode active component is selected from one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide, nickel manganese binary material and lithium nickel cobalt aluminum oxide; the oxide solid electrolyte is selected from one or more of lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide and lithium phosphorus oxygen nitrogen and their dopants.

[0017] The present invention provides a solid-state lithium metal battery, comprising the positive electrode sheet, the negative electrode sheet and the separator described in the above technical solution.

[0018] The invention provides a three-dimensional network polymer gel electrolyte, which comprises, by mass fraction, 80-98% of an organic solvent, 5-15% of a lithium salt, 2-8% of a lignin sulfonate, 2-10% of a polymerized monomer and 2-8% of an ionic liquid; the polymerized monomer is selected from one or more of polyethylene glycol diacrylamide, polyethylene glycol diacrylate, methyl methacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, vinyl acetate, vinyl sulfite, acrylamide, ethyl acrylate, tetrahydrofuran acrylate, 3-(isomethacryloyloxy)propyltrimethoxysilane, vinyl-tri(methylethylketoxime)silane and isooctyl acrylate. In the present invention, under the condition of ultraviolet light, lignin sulfonate can spontaneously generate quinone-based photochemical free radicals and hydroxyl photochemical free radicals in a mixed solution of ionic liquid and polymer monomers. Under the action of light free radicals, lignin sulfonate reacts with unsaturated double bonds on the polymer through phenol groups and is covalently linked together to form a gel electrolyte with a three-dimensional network structure, which can improve better mechanical strength and help inhibit the growth of lithium dendrites in lithium metal batteries, so that the metal lithium battery containing the gel electrolyte has excellent cycle life and safety performance. DETAILED DESCRIPTION

[0019] The present invention provides a three-dimensional network polymer gel electrolyte, which comprises, by mass fraction, 80-98% organic solvent, 5-15% lithium salt, 2-8% lignin sulfonate, 2-10% polymerized monomer and 2-8% ionic liquid;

[0020] The polymerizable monomer is selected from one or more of polyethylene glycol diacrylamide, polyethylene glycol diacrylate, methyl methacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, vinyl acetate, vinyl vinyl sulfite, acrylamide, ethyl acrylate, tetrahydrofuran acrylate, 3-(isomethacryloyloxy)propyltrimethoxysilane, vinyl-tri(methylethylketoxime)silane and isooctyl acrylate.

[0021] In the present invention, under the condition of ultraviolet light, lignin sulfonate can spontaneously generate quinone-based photochemical free radicals and hydroxyl photochemical free radicals in a mixed solution of ionic liquid and polymer monomers. Under the action of light free radicals, lignin sulfonate reacts with unsaturated double bonds on the polymer through phenol groups and is covalently linked together to form a gel electrolyte with a three-dimensional network structure, which can improve better mechanical strength and help inhibit the growth of lithium dendrites in lithium metal batteries, so that the metal lithium battery containing the gel electrolyte has excellent cycle life and safety performance.

[0022] The three-dimensional network polymer gel electrolyte provided by the present invention comprises 80-98% of an organic solvent; the organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl propionate, fluoroethylene carbonate and methyl trifluoroethyl carbonate.

[0023] The three-dimensional network polymer gel electrolyte provided by the present invention includes 5-15% lithium salt; the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalate borate, lithium perchlorate, lithium bis(oxalate borate), lithium tetrafluorooxalate phosphate and lithium difluorobis(oxalate)phosphate. The abundant polar groups such as hydroxyl groups present in lignin sulfonates can provide more active sites, thereby promoting the transport of lithium ions and improving the kinetics of electrochemical reactions. In addition, these polar groups can be electrostatically adsorbed by Li+, promoting Li + The uniform deposition of Li can inhibit the formation of Li dendrites.

[0024] The three-dimensional network polymer gel electrolyte provided by the present invention includes 2-8% lignin sulfonate; the lignin sulfonate is selected from one or more of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate. The free radicals generated by lignin sulfonate under ultraviolet irradiation can be used to initiate free radical polymerization. No initiator needs to be added during the photoinitiated in-situ polymerization process, which can completely avoid the incompatibility between the initiator and the lithium metal negative electrode. The abundant polar groups such as hydroxyl groups present in lignin sulfonate can provide more active sites, thereby promoting the transport of lithium ions and improving the kinetics of electrochemical reactions. In addition, these polar groups can be Li + Electrostatic adsorption promotes Li + The uniform deposition of Li can inhibit the formation of Li dendrites.

[0025] The three-dimensional network polymer gel electrolyte provided by the present invention comprises 2 to 10% of a polymerized monomer; the polymerized monomer is a monomer containing a double bond; the polymerized monomer is selected from one or more of polyethylene glycol diacrylamide, polyethylene glycol diacrylate, methyl methacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, vinyl acetate, vinyl sulfite, acrylamide, ethyl acrylate, tetrahydrofuran acrylate, 3-(isomethacryloyloxy)propyltrimethoxysilane, vinyl-tri(methylethylketoxime)silane and isooctyl acrylate; in a specific embodiment, the polymerized monomer is selected from acrylamide, polyethylene glycol dimethacrylate, 3-(isomethacryloyloxy)propyltrimethoxysilane or tetrahydrofuran acrylate. The present invention constructs a gel electrolyte with a three-dimensional interpenetrating network structure by adopting the above-mentioned types of polymerized monomers and ionic liquids, and a UV-curing in-situ polymerization method for lignin sulfonate. The three-dimensional interpenetrating network structure has more excellent mechanical properties, is conducive to maintaining its structural stability during the battery cycle, and has a certain inhibitory effect on the formation of lithium dendrites, so that the metal lithium battery containing the gel electrolyte has excellent cycle life and safety performance.

[0026] The three-dimensional network polymer gel electrolyte provided by the invention comprises 2-8% of ionic liquid, and the ionic liquid is selected from imidazoles and / or pyrroles.

[0027] The present invention provides a positive electrode sheet, which is prepared by the following method:

[0028] The positive electrode current collector provided with the positive electrode active material layer is immersed in the three-dimensional network polymer gel electrolyte described in the above technical solution, taken out and photocured to obtain a positive electrode sheet.

[0029] The positive electrode active material layer of the present invention comprises a positive electrode active material, a conductive agent and a binder; the positive electrode active material is a positive electrode active component coated with an oxide solid electrolyte; the positive electrode active component is selected from one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide, nickel manganese binary material and lithium nickel cobalt aluminum oxide; the oxide solid electrolyte is selected from one or more of lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide and lithium phosphorus oxygen nitrogen and dopants thereof. The coating amount of the oxide solid electrolyte in the positive electrode active component coated with the oxide solid electrolyte is 2 to 20 wt%.

[0030] In the present invention, the conductive agent is selected from one or more of conductive graphite, carbon nanotubes and graphene; the binder is selected from polyvinylidene fluoride and / or styrene-butadiene rubber.

[0031] In the present invention, the mass ratio of the positive electrode active material, the conductive agent and the binder is 80-98:1-10:1-10.

[0032] The positive electrode current collector provided with a positive electrode active material layer in the present invention is prepared according to the following method:

[0033] The positive electrode slurry is coated on the positive electrode current collector and then dried to obtain the positive electrode current collector provided with a positive electrode active material layer.

[0034] The positive electrode current collector used in the present invention is aluminum foil. The positive electrode current collector provided with a positive electrode active material layer is immersed in the three-dimensional network polymer gel electrolyte for 3 to 5 hours at a temperature of 20 to 30°C.

[0035] The ultraviolet light source used in the photocuring of the present invention is 365nm, and the intensity is 160-180mW cm -2 The light curing time is 15 to 25 minutes. In the specific embodiment, the wavelength of the ultraviolet light source is 365 nm and the intensity is 170 mW cm -2 ; The photocuring time is 20min. The present invention constructs a gel electrolyte with a three-dimensional interpenetrating network structure by using the above-mentioned types of polymerized monomers and ionic liquids, and a UV-curing in-situ polymerization method for lignin sulfonate. The three-dimensional interpenetrating network structure has more excellent mechanical properties, which is conducive to maintaining its structural stability during the battery cycle, and also has a certain inhibitory effect on the formation of lithium dendrites, so that the metal lithium battery containing the gel electrolyte has excellent cycle life and safety performance. In addition, the free radicals generated by lignin sulfonate under ultraviolet irradiation can be used to initiate free radical polymerization. No initiator needs to be added during the photo-initiated in-situ polymerization process, which can completely avoid the incompatibility of the initiator with the lithium metal negative electrode, thereby causing the adverse effects of related reactions on the lithium metal battery. Compared with the traditional casting method, the UV curing method uses more uniform ultraviolet radiation, so the gel uniformity is better, the gel time is also shorter, and the time cost is greatly saved. At the same time, the three-dimensional network polymer produced under high-power ultraviolet irradiation also has good wettability and thermal stability.

[0036] The present invention provides a solid-state lithium metal battery, comprising the positive electrode sheet, the negative electrode sheet and the separator described in the above technical solution.

[0037] The positive electrode sheet, the negative electrode sheet and the separator of the present invention are stacked and / or wound to obtain a bare battery cell; the bare battery cell is subjected to high-temperature formation, hot and cold pressing, degassing and vacuum packaging to obtain a solid-state lithium metal battery.

[0038] The diaphragm of the present invention is baked before lamination and / or winding, the baking temperature is 40°C to 120°C, and the processes before formation are all carried out in a drying room with a dew point less than -35°C.

[0039] The negative electrode plate in the present invention is metallic lithium.

[0040] The solid-state lithium battery provided by the present invention has excellent cycle performance and safety performance because the positive electrode plate contains the three-dimensional network polymer gel electrolyte described in the above technical solution.

[0041] In order to further illustrate the present invention, a three-dimensional network polymer gel electrolyte, a positive electrode sheet and a solid-state lithium battery provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0042] Example 1

[0043] Step 1: Mix the organic solvent, lithium salt, lignin sulfonate, ionic liquid, polymer monomer, etc. in a certain proportion and stir until a uniform and transparent gel electrolyte mixture is formed. The organic solvent is fluorinated ethylene carbonate and dimethyl carbonate, accounting for 20wt% and 62wt% of the gel electrolyte mixture, respectively. The lithium salt is a mixed lithium salt of lithium difluorooxalate borate and lithium hexafluorophosphate, which account for 0.2wt% and 12wt% of the gel electrolyte mixture, respectively. The polymer monomer is acrylamide, which accounts for 2.0wt% of the gel electrolyte mixture. The lignin sulfonate is sodium lignin sulfonate, and the ionic liquid is 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt (EMI-TFSI), which account for 2.0wt% and 2.0wt% of the gel electrolyte mixture, respectively.

[0044] Step 2: Select 5wt% lithium aluminum titanium phosphate (Li 1.2 Al 0.2 Ti 1.8 The positive electrode sheet was baked at 90°C for 24 hours, immersed in the mixed solution for 4 hours, and then taken out and exposed to a UV LED light source (365nm, 170mW cm -2 ) was photocured for 20 minutes to obtain a positive electrode sheet coated with a three-dimensional network polymer gel electrolyte.

[0045] Step 3: The positive electrode sheet coated with the three-dimensional network polymer gel electrolyte is stacked and / or wound with the metal lithium negative electrode and the conventional PE / PP separator to obtain a bare cell, and the bare cell is packaged to obtain a solid lithium metal cell, and the bare cell is placed in an outer package without the need to inject additional electrolyte. After packaging, standing, heating, formation, hot and cold pressing, degassing and vacuum packaging, the solid lithium metal battery is prepared.

[0046] Example 2

[0047] The difference from Example 1 is that the polymer monomer is polyethylene glycol dimethacrylate, and the rest is the same as Example 1.

[0048] Example 3

[0049] The difference from Example 1 is that the polymer monomer is 3-(isomethacryloyloxy)propyltrimethoxysilane, and the rest is the same as Example 1.

[0050] Example 4

[0051] The difference from Example 1 is that the polymer monomer is tetrahydrofuran acrylate, and the rest is the same as Example 1.

[0052] Comparative Example 1

[0053] Step 1: Mix the organic solvent, lithium salt, ionic liquid, initiator and polymer monomer in a certain proportion and stir until a uniform and transparent gel electrolyte mixture is formed. The organic solvent is fluorinated ethylene carbonate and dimethyl carbonate, accounting for 20wt% and 64wt% of the gel electrolyte mixture, respectively. The lithium salt is a mixed lithium salt of lithium difluorooxalate borate and lithium hexafluorophosphate, which account for 0.2wt% and 12wt% of the gel electrolyte mixture, respectively. The polymer monomer is pentaerythritol tetraacrylate and polyethylene glycol dimethacrylate, accounting for 2.0wt% and 2.0wt% of the gel electrolyte mixture, respectively. The ionic liquid is 1-ethyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt (EMI-TFSI), and the initiator is azobisisobutyronitrile, accounting for 2.0wt% and 0.1wt% of the gel electrolyte mixture, respectively.

[0054] Step 2: Select the same positive electrode sheet as in Example 1, bake the positive electrode sheet at 90°C for 24 hours, and stack and / or wind the metal lithium negative electrode and the conventional PE / PP separator in the embodiment to obtain a bare cell, package the bare cell to obtain a solid lithium metal cell, put the bare cell into an outer package, and inject a trace amount of gel electrolyte mixture. After packaging, standing, heating, formation, hot and cold pressing, degassing and vacuum packaging, the solid lithium metal battery is prepared.

[0055] Comparative Example 2:

[0056] Step 1: Mix the organic solvent, lithium salt, ionic liquid, lignin sulfonate, etc. in a certain proportion and stir until a uniform and transparent gel electrolyte mixture is formed. The organic solvent is fluorinated ethylene carbonate and dimethyl carbonate, accounting for 20wt% and 64wt% of the gel electrolyte mixture, respectively. The lithium salt is a mixed lithium salt of lithium difluorooxalate borate and lithium hexafluorophosphate, which account for 0.2wt% and 12wt% of the gel electrolyte mixture, respectively. The ionic liquid is 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonyl imide salt (EMI-TFSI), and the lignin sulfonate is sodium lignin sulfonate, accounting for 2.0wt% and 0.1wt% of the gel electrolyte mixture, respectively.

[0057] Step 2: Same as step 2 in comparative example 1.

[0058] Comparative Example 3:

[0059] The difference from Example 1 is that the polymer monomer is dimethyldiallylammonium chloride, and the rest is the same as Example 1.

[0060] The present invention conducts test experiments on the same batch of solid-state lithium metal batteries prepared in Examples 1 to 2 and the comparative example, respectively, with a voltage range of 3 to 4.2 V. The test results are shown in Table 1.

[0061] Table 1. Solid-state lithium metal battery performance test results

[0062]

[0063] According to the data in Table 1, it can be seen that, compared with the solid-state lithium metal batteries prepared in the comparative example, the solid-state lithium metal batteries prepared in Examples 1 to 4 of the present invention have better first efficiency, ionic conductivity, capacity utilization and cycle stability, and are not prone to short circuit, reflecting the good electrochemical stability and ionic conductivity of the three-dimensional network polymer gel electrolyte.

[0064] As can be seen from the above embodiments, the present invention provides a three-dimensional network polymer gel electrolyte, which includes 80-98% organic solvent, 5-15% lithium salt, 2-8% lignin sulfonate, 2-10% polymerized monomer and 2-8% ionic liquid by mass fraction; the polymerized monomer is selected from one or more of polyethylene glycol diacrylamide, polyethylene glycol diacrylate, methyl methacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, vinyl acetate, vinyl sulfite, acrylamide, ethyl acrylate, tetrahydrofuran acrylate, 3-(isomethacryloyloxy)propyltrimethoxysilane, vinyl-tri(methylethylketoxime)silane and isooctyl acrylate. Lignin sulfonate is mainly derived from acidic and neutral sulfite pulping wastewater and is a high molecular polymer with a large number of hydrogen bonds and a network structure. A large number of phenolic hydroxyl groups, alcoholic hydroxyl groups, sulfonic acid groups, methoxyl groups and other groups exist in the lignin sulfonate molecules, which can undergo a series of chemical reactions such as oxidation, sulfonation, hydroxymethylation, and can also undergo polycondensation or self-condensation with other substances. In the present invention, under the condition of ultraviolet light, the lignin sulfonate can spontaneously generate quinone-based photochemical free radicals and hydroxyl photochemical free radicals in a mixed solution of ionic liquid and polymer monomers. Under the action of light free radicals, the lignin sulfonate reacts with the unsaturated double bonds on the polymer through the phenolic group, and is covalently linked together to form a gel electrolyte with a three-dimensional network structure, which can improve better mechanical strength, help inhibit the growth of lithium dendrites in lithium metal batteries, and make the metal lithium battery containing the gel electrolyte have excellent cycle life and safety performance.

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A three-dimensional network polymer gel electrolyte, characterized in that: Calculated by mass fraction, it includes 80-98% organic solvent, 5-15% lithium salt, 2-8% lignin sulfonate, 2-10% polymer monomer and 2-8% ionic liquid; The polymerizable monomer is selected from one or more of polyethylene glycol diacrylamide, polyethylene glycol diacrylate, methyl methacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, vinyl acetate, vinyl vinyl sulfite, acrylamide, ethyl acrylate, tetrahydrofuran acrylate, 3-(isomethacryloyloxy)propyltrimethoxysilane, vinyl-tri(methylethylketoxime)silane and isooctyl acrylate.

2. The three-dimensional network polymer gel electrolyte according to claim 1, characterized in that: The lignin sulfonate is selected from one or more of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate.

3. The three-dimensional network polymer gel electrolyte according to claim 1, characterized in that: The ionic liquid is selected from imidazoles and / or pyrroles; The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, lithium perchlorate, lithium bisoxalatoborate, lithium tetrafluorooxalatophosphate and lithium difluorobisoxalatophosphate.

4. The three-dimensional network polymer gel electrolyte according to claim 1, characterized in that: The organic solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl propionate, fluoroethylene carbonate, and methyl trifluoroethyl carbonate.

5. A positive electrode sheet, prepared by the following method: The positive electrode current collector provided with a positive electrode active material layer is immersed in the three-dimensional network polymer gel electrolyte according to any one of claims 1 to 4, taken out and then photocured to obtain a positive electrode sheet.

6. The positive electrode sheet according to claim 5, characterized in that: The immersion time is 3 to 5 hours; the immersion temperature is 20° C. to 30° C.

7. The positive electrode sheet according to claim 5, characterized in that: The ultraviolet light source used in the photocuring is 365nm and the intensity is 160-180mW cm -2 ; The light curing time is 15 to 25 minutes.

8. The positive electrode sheet according to claim 5, characterized in that: The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder; The positive electrode active material is a positive electrode active component coated with an oxide solid electrolyte; the positive electrode active component is selected from one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese oxide, nickel manganese binary material and lithium nickel cobalt aluminum oxide; the oxide solid electrolyte is selected from one or more of lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide and lithium phosphorus oxygen nitrogen and their dopants.

9. A solid-state lithium metal battery, comprising the positive electrode sheet, the negative electrode sheet and the separator according to any one of claims 5 to 8.

Citation Information

Cited By

  • Three-dimensional solid-state lithium battery and preparation method thereof

    CN119833706A

  • Lithium metal battery and manufacturing method thereof, battery device, energy storage device and power utilization device

    CN120999143A

  • Gel polymer electrolyte, preparation method of gel polymer electrolyte, lithium battery and preparation method of lithium battery

    CN121331933A

  • Electrolyte film, preparation method thereof and lithium battery

    CN122338226A

  • Electrolyte film, method for manufacturing the same, and lithium battery

    CN122338226B